Ten-year hemoglobin A1c trajectories and outcomes in Type 2 diabetes mellitus: The Diabetes & Aging Study - Laiteerapong, Neda (J Diabetes Complications, 2016)
AIMS: To classify trajectories of long term HbA1c values in patients after diagnosis of Type 2 diabetes and examine each trajectory's associations with subsequent microvascular and macrovascular events and mortality. METHODS: Longitudinal follow-up of 28,016 patients newly diagnosed with Type 2 diabetes. Latent growth mixture modeling to identify ten-year HbA1c trajectories. Cox proportional hazards models to assess how HbA1c trajectories were associated with events (microvascular and macrovascular) and mortality. RESULTS: We identified 5 HbA1c trajectories: “low stable” (82.5%), “moderate increasing late” (5.1%), “high decreasing early” (4.9%), “moderate peaking late” (4.1%) and “moderate peaking early” (3.3%). After adjusting for average HbA1c, compared to the low stable trajectory, all non-stable trajectories were associated with higher incidences of microvascular events (hazard ratio (HR) range, 1.28 (95% CI, 1.08-1.53) (high decreasing early) to 1.45 (95% CI, 1.20-1.75) (moderate peaking early). The high decreasing early trajectory was associated with an increased mortality risk (HR, 1.27 (95% CI, 1.03-1.58)). Trajectories were not associated with macrovascular events. CONCLUSIONS: Non-stable HbA1c trajectories was associated with greater risk of microvascular events and mortality. These findings suggest a potential benefit of early diabetes detection, prioritizing good glycemic control, and maintaining control over time.